PERBANDINGAN MEDIA PEMBELAJARAN POWTOON DAN POWERPOINT MENGGUNAKAN MODEL INQUIRY LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MATEMATIKA DI SMAN 1 AROSBAYA - Arimby Hariananda, Dena; Kusmiyati; Victor Maruli T. L. T (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study compares the effectiveness of Powtoon and PowerPoint as learning media in the Inquiry Learning model on students’ creative thinking skills in mathematics. Creative thinking skills were measured based on fluency, flexibility, originality, and elaboration. The research employed a quantitative approach with a quasi-experimental design. The sample consisted of two eleventh-grade classes at SMAN 1 Arosbaya, each with 30 students. The research instrument was an essay-based creative thinking test, which was validated for reliability and validity. Data analysis utilized the t-test (paired sample test and independent sample test) using SPSS 25. The results showed that: (1) there was a significant difference in students' creative thinking skills before and after using Powtoon; (2) there was a significant difference before and after using PowerPoint; and (3) Powtoon was more effective than PowerPoint in enhancing students' creative thinking skills. This study concludes that the use of technology-based learning media can enhance students' creative thinking skills, with Powtoon having a more significant impact than PowerPoint. These findings have implications for educators in selecting more interactive and innovative learning media to foster students’ creative thinking skills in mathematics.